PUBLIC’S LITERATE OF INTERNET FOR IMPLEMENTING E-PUBLIC SERVICE IN DELI SERDANG DISTRICT, NORTH SUMATRA - Marudur P. Damanik (Pusbindiklat - LIPI, 2012)
Implementing public service based on e-government (e-public service) requires a good literate in ICT especiallyin accessing the internet. This study aimed to describe the public’s knowledge level in ICT so that thelocal government can use appropriate strategy in establishing the e-public service. After collecting data from 100people in Deli Serdang District, North Sumatra, this research discovers that people’s knowledge in acccessing theinternet is relatively low, which 44% of respondents are totally unable to access the internet.